Mapas conceituais como ferramentas para complementação ao ensino - aprendizagem das proteínas - Silva, Karla Nunes da (2011)
This project aimed to investigate whether concept maps can leverage and interfere positively on the teaching-learning process in lessons about proteins, in the case of high school students from a public school in the city of Manaus. For that, it was considerate other studies witch link the use of concept maps and other areas of knowledge. In addition, the research was developed with the elaboration of a didactic sequence, where tests were performed prior and subsequent to verify whether the activity on concept maps, it prepared by students were potentially useful for the establishment and development of their knowledge. It was performed a quantitative analysis, which included the order of fulfils and a comparative study of these data, taking as the comparison group activities with students in higher education, aiming to validate the research proposal. It was also made a qualitative analysis, where the concept maps produced by high school students were categorized according to the level of concept relationships, thus explaining the difficulties encountered. The use of concept maps for teaching in high school and university showed that the organization and discussion of concepts in the classroom makes it possible to clarify and minimize the doubts broth from the students about the subject of study. Furthermore, in despite of initial difficulties, the students after finishing the activity showed interest in constructions of concept maps, providing the greatest benefit as an incentive to read and systematization of new knowledge. Thus, it was checked for possible contribution of conceptual maps as a resource for teaching and learning about proteins, including serving as a resource evaluation for the teacher, so he can also make a screening of his boarding and not only verify the student's knowledge, but the scope of the operations and the detection of possible failures be corrected in teaching. The research culminated in a production of a homepage, with guidance material for construction activities of concept maps and teaching about Science.